Effects of Dietary Substitution of Alfalfa Silage with Virginia Fanpetals Silage in Lactating Polish Holstein Friesian Dairy Cows - Purwin, Cezary (Animals (Basel), 2020)
SIMPLE SUMMARY: Alfalfa silage, owing to its chemical composition, complements maize silage in many rations for dairy cows. The disadvantages of alfalfa are the high soil requirements, agrotechnical treatments and sensitivity to cold and flooding. Many dairy farms are unable to grow alfalfa because of poor quality of the soils, and grass crops are unreliable due to increasing drought. For this reason, alternative plants are being sought out to produce feeds for dairy cows. So far, Virginia fanpetals has been used as an energy source, but thanks to its high levels of protein (17–25%), the possibility of using it in cattle feed has been recognized. Virginia fanpetals grows well in poor quality soils, in difficult climatic conditions (frost, drought), with no need for annual treatments, and the harvest is carried out with maize harvesting equipment. To date, no studies have been carried out on the possibility of replacing alfalfa with Virginia fanpetals in the diets of dairy cows. Based on our results, it was concluded that Virginia fanpetals is a good source of protein and can be a substitute or supplement to alfalfa silage. The best production results were obtained with half-substitution of alfalfa silage by Virginia fanpetals silage in diets based on maize silage. ABSTRACT: The aim of this study was to evaluate the effect of partial or complete substitution of alfalfa silage with Virginia fanpetals silage in rations based on maize silage on feed intake, digestibility, ruminal fermentation and milk yield and physicochemical characteristics. Nine Polish Holstein Friesian cows in the second half of lactation were fed three experimental diets in a replicated 3 × 3 Latin square design as follows: maize silage + alfalfa silage, maize silage + alfalfa silage and Virginia fanpetals silage in a 50:50 ratio, maize silage + Virginia fanpetals silage. Complete substitution caused an increase in dry matter intake (DMI), total volatile fatty acids (VFA), acetic acid to propionic acid (A/P) ratio, N-NH(3) in the rumen contents and milk urea and a decrease in the feed conversion ratio. The partial and complete substitution changed the profile of milk fatty acids, resulting in a slight increase in saturated fatty acids (SFA) and a decrease in unsaturated fatty acids (UFA) as well as in all functional fatty acids except vaccenic acid. The most promising production effects were achieved through partial substitution of alfalfa silage with the Virginia fanpetals silage.